Composition and Water Ecology Indication of Functional Feeding Groups of Zoobenthos in Liuxi River - CHEN Ci; ZHU Kunpeng; LIU Yue; LI Jiaxu; TAN Ying; WANG Lu (Renmin Zhujiang)
The Liuxi River is the most important river system in Guangzhou,and systematic monitoring and assessment provide basic information for the health management of the Liuxi River ecosystem.Field in-situ sampling of zoobenthos in the Liuxi River was conducted during the dry (March) and wet (September) seasons in 2019 to explore the spatio-temporal distribution characteristics of functional feeding groups (FFGs) of zoobenthos,and the habitat conditions of the Liuxi River were assessed by the composition of the zoobenthos FFGs.The results show that the main group of zoobenthos in the Liuxi River Basin is collectors,followed by scrapers and predators,whereas filterers and shredders are rarely observed.The dominant groups at the sampling sites in the upper and middle reaches are moderate pollution tolerant collectors (Baetidae and Corbiculidae) and pollution tolerant collectors (Chironomidae),while the sampling sites in the lower reaches are overwhelmingly dominated by pollution tolerant collectors (Chironomidae).Environmental factors significantly affect the distribution of zoobenthos FFGs.Specifically,the key environmental factors in the dry season are velocity and NO3,while those in the wet season are SiO2 and velocity.The attributes of the Liuxi River ecosystem were analyzed on the basis of the composition of the zoobenthos FFGs.The results indicate that the ecosystems at most of the sampling sites in the Liuxi River are heterotrophic ones,and the riparian zone of this basin is not healthy.The longitudinal transport ability of the river is mostly in an unhealthy state.Predators' control effect is normal except at some sampling sites in the upper reaches.The basin maintains favorable habitat stability except at the sampling sites affected by sand dredging.